ANALISIS PENANGANAN KELUHAN TAMU DI EXPRESS RESTAURANT HOTEL HOLIDAY INN RESORT BARUNA BALI - Saputra, Kadek Dani Yoga; Andayani, Ni Luh Henny (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze guest complaint handling at Express Restaurant, Holiday Inn Resort Baruna Bali, using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving staff, trainees, daily workers, and restaurant managers. The results show that the most common complaints are attitudinal complaints and service-related complaints, such as unfriendly staff behavior, delayed food service, and incorrect orders. Key obstacles include lack of specific training, high workload during breakfast hours, and limited communication skills with foreign guests. Management addresses these issues through strategies based on the five SERVQUAL dimensions, including communication training, SOP enforcement, mobile manager presence, and fostering empathy. Responsive and structured complaint handling has proven to enhance guest satisfaction and loyalty. The findings are expected to serve as a reference for improving restaurant service quality through a humanistic and systematic approach.